Pelatihan Keterampilan Kesehatan Senam Yoga Untuk Menurunkan Nyeri Disminore Pada Remaja Putri - Yanti, Fitri - (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2025)
Abstract In general, women experience pain, and some also experience menstrual pain with varying degrees of severity. The prevalence of dysmenorrhea in Indonesia is 64.25%, including primary dysmenorrhea at 54.8% and secondary dysmenorrhea at 9.36%. The impact of menstrual pain (dysmenorrhea) in adolescent girls not being addressed can disrupt daily activities, cause anxiety, stress, irregular menstrual cycles, and even other diseases. Yoga is a technique that teaches deep breathing techniques, relaxation, and body positions to increase strength, balance, and reduce pain. The purpose of this training is to reduce the prevalence of dysmenorrhea pain cases in adolescent girls at Posyandu Lestari 3 Tanjung Raya Kedamaian Bandar Lampung, a total of 20 people in Tanjung Raya Bandar Lampung. The results of this training showed that there was an average result before the yoga exercise movement, getting 1.15 while the average result after being given yoga exercise movement was 8.8. So the results obtained showed an increase in results reaching 6.25, this proves that the results of community service activities regarding yoga exercise counseling to reduce menstrual pain (dysmenorrhea) showed an increase in knowledge and understanding that had been provided. Â Keywords : Training, Skills, Health